The concrete plateau urban Tibetans and the Chinese civilizing machine - Grant, Andrew, 1984- (Studies of the Weatherhead East Asian Institute, Columbia University., 2022)
"The Concrete Plateau discusses Tibetans' migration to Xining, a large city on the eastern Tibetan Plateau. Although twenty-first-century urban planning in Xining has made the city more similar to other cities across China, Tibetans nevertheless use urban resources and networks to create a subaltern Tibetan city that sustains their identity"--